PERAN KEPALA SEKOLAH SEBAGAI ADMINISTRATOR DI SD NEGERI 94/IV KOTA JAMBI - Hizkia Manurung; Akhmad Habibi; Hansein Arif Wijaya (Inteligensi : Jurnal Ilmu Pendidikan, 2026)
This study aims to examine the role of the principal as an administrator at SD Negeri 94/IV Kota Jambi and the challenges faced in its implementation. This research uses a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, and analyzed inductively to gain an in-depth understanding of the phenomenon. The results show that the principal has carried out administrative roles in various aspects, including curriculum administration, student administration, personnel administration, facilities and infrastructure, archiving, and financial administration. The implementation of administration is conducted through planning, organizing, and supervising functions in a systematic and structured manner. However, several challenges remain, such as limited budget, human resources, and inadequate facilities and infrastructure. In conclusion, the principal’s role as an administrator has been implemented well, but still requires optimization through better resource management and stronger support to achieve more effective and sustainable school administration.